2020
DOI: 10.1111/1346-8138.15285
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of lymph node dissection in the treatment of extramammary Paget’s disease: A single‐institution study

Abstract: Extramammary Paget's disease (EMPD) often invades the dermis and metastasizes to the lymph nodes. Patients with EMPD associated with lymph node metastases have poor prognosis; to date, effective treatment has not yet been established. Lymph node dissection, aiming to control the local disease, is a standard form of management for EMPD patients with lymph node metastases (LNM). We investigated the clinical and pathological features, treatment strategies and prognostic factors of patients with metastatic EMPD wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…We also excluded 19 other patients presenting with ≤2 LN metastases. Finally, 26 patients with ≥3 LN metastases were included in the current study due to their poor prognoses, according to the results of previous reports 5–7 . EMPD diagnosis was pathologically confirmed by a board‐certified dermatologist and a board‐certified pathologist.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also excluded 19 other patients presenting with ≤2 LN metastases. Finally, 26 patients with ≥3 LN metastases were included in the current study due to their poor prognoses, according to the results of previous reports 5–7 . EMPD diagnosis was pathologically confirmed by a board‐certified dermatologist and a board‐certified pathologist.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have also shown that the number of LN metastases predicts survival 4 . For example, the prognoses of patients with ≥3 LN metastases are significantly worse compared to those with fewer metastases; the 5‐year survival rates for patients with 2 and ≥3 LN metastases have been reported to be 77.8%–100% and 0%–20%, respectively 5–7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-year survival rate was 100% and 19.1% in patients with two or less LN metastases and with three or more LN metastases, respectively. They also found that, in patients with three or more LN metastases, the 5-year survival rate after adjuvant radiation therapy was better than that after surgery alone, indicating that adjuvant radiation therapy for EPMD cases with three or more regional LN metastases may improve the prognosis [127].…”
Section: Treatment For Regional Ln Metastasesmentioning
confidence: 98%
“…LN dissection is a standard form of management for regional LN metastases in EMPD, although there is a lack of evidence showing that the LN dissection significantly improves overall survival in such patients. Tsutsui et al analyzed patients with metastatic EMPD who underwent LN dissection, and their multivariate analysis revealed that the number of metastatic LNs was an independent prognostic factor for overall survival [127]. The 5-year survival rate was 100% and 19.1% in patients with two or less LN metastases and with three or more LN metastases, respectively.…”
Section: Treatment For Regional Ln Metastasesmentioning
confidence: 99%